Al-Nafs dalam Filsafat Islam: Kajian Kritis terhadap Pemikiran tentang Jiwa: Al-Nafs in Islamic Philosophy: A Critical Study of Thought about the Soul - Salam, Andi Muhammad Ikbal; Huzain, Muhammad (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
This study discusses a critical study of thoughts about the al-nafs (soul) in Islamic philosophy by focusing on three sub-problems, namely: 1) Muslim philosophers' thoughts about the al-nafs (soul); 2) study of the soul regarding the purpose of human life; and 3) thoughts about the soul in the tradition of Islamic philosophy. This type of research is a literature review with a philosophical approach. data collection methods using documentation and data analysis techniques using content analysis. The results show that the word of al-nafs (soul) in the Qur'an is sometimes interpreted as a spirit, and not vice versa, this shows that al-nafs (soul) originates from the spirit. The spirit is the essence and the soul is part of the spirit. The philosophy of al-nafs (soul) which was proposed by Muslim philosophers was a seepage of Greek philosophy which they then perfected with a normative theological approach (al-Qur'an and hadith). According to Muslim philosophers, the soul is a spiritual esoteric substance as a form for the body. The relationship of the unity of the soul with the body is an accidental unity, in which both stand alone and have different substances, so that the death of the body does not bring death to the soul.